Management of Hirsutism and Acne in Women with Polycystic Ovary Syndrome: A Narrative Review of Current Evidence and Emerging Therapies - Papuga, Aleksandra; Hejduk, Makary; Makowska, Joanna; Darmoń, Jerzy; Piegza, Natalia; Domańska, Karolina; Sieczka, Anna; Windyga, Maria; Bury, Justyna (Quality in Sport, 2026)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age and is frequently associated with hyperandrogenic manifestations, including hirsutism and acne. These symptoms significantly impair quality of life and are closely linked to metabolic dysfunction, insulin resistance, and hormonal imbalance. The heterogeneous nature of PCOS contributes to variability in treatment response and complicates the development of optimal therapeutic strategies. Aim: This narrative review aimed to evaluate current therapeutic approaches for hirsutism and acne in women with PCOS, focusing on clinical efficacy, mechanisms of action, and future therapeutic perspectives. Materials and Methods: A narrative review of the literature was conducted using PubMed/MEDLINE and Google Scholar databases. Publications from 2015–2026 were analyzed, including randomized controlled trials, systematic reviews, meta-analyses and international clinical guidelines. Results: Combined oral contraceptives remain the first-line treatment for hirsutism and acne due to their efficacy in reducing androgen excess and regulating menstrual cycles. Antiandrogens, particularly spironolactone, effectively reduce hirsutism, whereas metformin primarily improves metabolic abnormalities and insulin resistance. Emerging evidence suggests that GLP-1 receptor agonists may provide additional benefits through weight reduction, improved insulin sensitivity, and decreased androgen levels. However, current evidence is limited by heterogeneity of study populations, varying diagnostic criteria, short follow-up periods and lack of standardized outcome measures. Conclusions: Management of hirsutism and acne in PCOS requires an individualized and multidimensional therapeutic approach. Further high-quality long-term studies are needed to optimize treatment strategies and improve clinical outcomes.